Pengaruh Cisco Packet Tracer terhadap Pemahaman Konsep Jaringan Komputer di SMK Telkom Makassar - A. Alfatira Nur Aisah (Sakura Digital Nusantara, 2025)
This study aims to evaluate the effect of using a Network Simulation Tool on students' understanding of computer network concepts in Grade XI at SMK Telkom Makassar. The research method used was quantitative with a pre-experimental design. The research subjects consisted of 32 students who were given materials on IP Address, Routing, and Subnetting, followed by a pre-test before practicing with the Network Simulation Tool, and a post-test afterward. The results showed an increase in the students' average scores from 23.87 in the pre-test to 35.22 in the post-test. Data distribution was found to be normal based on the Kolmogorov-Smirnov test, with significance values of 0.139 for the pre-test and 0.114 for the post-test (both > 0.05). The Paired Sample T-Test showed a significance value of 0.000 (< 0.05), indicating a significant difference in students’ understanding before and after the intervention. In detail, there was an increase in understanding in the following domains: Routing Static & Dynamic by 18.44%, IP Address & Subnetting by 25.53%, Routing Static in Cisco Packet Tracer by 48.05%, Subnetting (calculation & configuration) by 29.68%, and Routing & Connection (troubleshooting) by 10.94%.